2013
DOI: 10.1155/2013/782609
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Some Protozoan Parasites Causing Infertility in Farm Animals

Abstract: The paper reviews some protozoan parasites responsible for infertility in livestock with specific emphasis on neosporosis, sarcocystosis, toxoplasmosis, and trichomoniasis. It highlights the transmission, pathogenesis, clinical signs, diagnosis, prevention, control, and treatment of the individual parasite. It is concluded that these parasites are often overlooked during investigation into causes of abortion in livestock, and they may, however, be responsible for some infertilities in this group of animals whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Concerning the difference among age groups, results showed that the differences were not significant (Table 2). These results supported the previous results obtained by Kanyari et al, (2010) and Wisesa et al, (2015). Meanwhile, our results disagreed with the results of Roy et al, and Al-Jaderia).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Concerning the difference among age groups, results showed that the differences were not significant (Table 2). These results supported the previous results obtained by Kanyari et al, (2010) and Wisesa et al, (2015). Meanwhile, our results disagreed with the results of Roy et al, and Al-Jaderia).…”
Section: Resultssupporting
confidence: 94%
“…The association between gender and infection was not significant. The result is consistent with the result obtained by Kanyari et al, (2010) and Singh et al, (2012) in cattle which supported to the earlier finding of Azhar et al, (2002) who reported both male and female buffalo have the same chance of being infected with the Fasciola sp. However, the result of this study contrasted with the result obtained by Wisesa et al, (2015) who found that the infection rate of balantidiasis in cattle was significantly (p<0.05) higher in male (23.20%) than female (13.72%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Protozoan parasites are a significant cause of abortion and infertility in domestic ruminants (Kaltungo and Musa, 2013). Toxoplasma gondii infection in sheep is distributed worldwide and is responsible for considerable economic losses.…”
Section: Semen Contamination With Protozoamentioning
confidence: 99%
“…Neospora spp., obligate intracellular parasite related to Toxoplasma gondii, has emerged as an important cause of reproductive disease, especially as an abortifacient in cattle (Kaltungo and Musa, 2013;Syed-Hussain et al, 2013). In sheep, the first natural infection of Neospora caninum was identified in 1990 in a congenitally infected lamb with signs of ataxia and weakness after birth; repeated abortions in subsequent years have also been reported.…”
Section: Semen Contamination With Protozoamentioning
confidence: 99%